'Meal' and its relating words in English and in Vietnamese from semantic and cultural perspectives / Duong Van Hoat; Supervisor: Assoc. Prof. Dr. Hoang Tuyet Minh - Duong, Van Hoat
The study focuses on solving the major question of what the primary similarities and differences between the word ‘meal’ and its relating words in English and in Vietnamese are from semantic and cultural perspectives. It is based on the wide range of methods namely contrastive, comparative as well as synthetic methods conducted by collecting data, analyzing the data, and drawing representative conclusion. The data from books, newspapers, articles, magazines on the internet and in daily lives are collected and analyzed by the writer and are studied in the light of semantic and cultural perspectives. After being documented, the writer analyzes them, as a result, the semantic and cultural features of ‘Meal’ and its fields are identified, explained and clarified namely names of meals, parts of the meals, eating means, eating places and dining etiquettes in both England and Vietnam. From the result of the study, it is attempted to explore how ‘meal’ and its relevant words are realized in English learning and application on a daily basis with the hope that it will help the readers to recognize the importance of mastering ‘Meal’ and its relating words in English and in Vietnamese in the light of semantics and culture in teaching and learning English for thorough awareness and better findings. Additionally, the study helps with correcting students’ mistakes in word use and enables having a better understanding of schools of words about meal and relevant words in English and Vietnamese as well; therefore, the study bears a great potential of becoming a basis for other authors to make more intensive researches in the future.